Oral contraception does not alter typical post-exercise interleukin-6 and hepcidin levels in females. Issue 1 (January 2015) - Sim, Marc; Dawson, Brian; Landers, Grant; Swinkels, Dorine W.; Tjalsma, Harold; Yeap, Bu B.; Trinder, Debbie; Peeling, Peter
Abstract Objectives The post-exercise interleukin-6 (IL-6) and hepcidin response was investigated during the hormone-deplete and hormone-replete phases of an estradiol and progestogen regulated oral contraceptive cycle (OCC). Design Counterbalanced, repeated measures cross-over study. Methods Ten active female monophasic oral contraceptive pill (OCP) users completed two 40 min treadmill running trials at 75% of their pre-determined peak oxygen uptake velocity (vVO2peak). These trials were randomly performed in two specific phases of the OCC: (a) Day 2–4, representing a hormone-free withdrawal period (D − 0); (b) Day 12–14, representing the end of the first week of active hormone therapy (D + 7). Venous blood samples were drawn pre-, post- and 3 h post-exercise. Results In both trials, serum IL-6 was significantly elevated (p < 0.05) immediately post-exercise, while serum hepcidin was significantly elevated (p < 0.05) 3 h post-exercise, with no significant differences recorded between trials. Conclusions These findings suggest that exercise performed during the different phases (D − 0 vs. D + 7) of a monophasic OCP regulated cycle does not alter exercise induced IL-6 or hepcidin production. As such, future studies looking to investigate similar variables post-exercise, may not need to 'control' for different phases of the OCC, provided participants are current monophasic OCP users.